Study of Rural Industries Projects Design Schedules Etc. and Instructions - Planning Commission (Planning Commission, 1966)
The PEO studies will be gradually oriented towards the type of intensive case-study as being undertaken during the current year, we thought, therefore, that it would be appropriate to bring together in the form of a booklet all the methodological papers including objective, scope, sample, schedules etc. and instructions for the convenience of the investigating officers.
Programme Evaluation Organisation Planning Commission